IMPLEMENTASI PELAYANAN KEKAYAAN INTELEKTUAL DALAM MENDUKUNG PERLINDUNGAN HAK CIPTA, MEREK, DAN PATEN MELALUI KEGIATAN MAGANG DI KEMENKUMHAM - Fantriansyah; Muhammad Aprian Jailani; Rahmad Hidayat (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Intellectual property plays a crucial role in providing legal protection for the creative and innovative outcomes of the community. However, the low level of public understanding regarding the importance of copyright, trademark, and patent protection poses a challenge to optimizing the utilization of the intellectual property system. Therefore, intellectual property services provided by the Ministry of Law and Human Rights play a strategic role in increasing public awareness and access to such legal protection. This study aims to describe the implementation of intellectual property services in supporting copyright, trademark, and patent protection through internships at the Regional Office of the Ministry of Law and Human Rights in West Nusa Tenggara. This study uses a qualitative approach with a descriptive research type. Data were obtained through observation, interviews, and documentation conducted during the internship, then analyzed using an interactive analysis model that includes data reduction, data presentation, and conclusion drawing. The results show that intellectual property services at the Ministry of Law and Human Rights in West Nusa Tenggara are implemented through consultation services, registration assistance, outreach, and facilitation of copyright, trademark, and patent applications. These services contribute to increasing public understanding, simplifying the registration process, and supporting legal protection for works and innovations. Although there are still obstacles such as low intellectual property literacy and limited understanding of registration procedures, various efforts to improve services continue to be made. Thus, the implementation of intellectual property services at the NTB Ministry of Law and Human Rights has played a positive role in strengthening the protection of the community's intellectual property rights.